Translation and validation of the caffeine use disorder questionnaire in Arabic - Feten Fekih-Romdhane; Rabih Hallit; Diana Malaeb; Fouad Sakr; Mariam Dabbous; Sahar Obeid; Souheil Hallit (Archives of Public Health, 2024)
Abstract Background Due to the elevated global prevalence of its consumption, and the detrimental health effects it can have, caffeine use disorder (CUD) should receive a great deal of attention from clinicians and the research community in Arab countries as an area of concern. To help advance the field, this study aimed to translate the Caffeine Use Disorder Questionnaire (CUDQ) into the Arabic language, and examine its psychometric properties in community adults. Methods A descriptive, observational and cross-sectional study was carried out during the period from May to July 2024. Arabic-speaking adults from the general population of Lebanon (N = 1858, 49.8% males, mean age of 30.05 ± 11.39 years), reporting caffeine consumption at least once during the last 12 months, were included. Results The study’s results provided support to the theoretical assumptions of unidimensionality of the original version of the CUDQ, with excellent composite reliability (Cronbach’s α = 0.90). Furthermore, the structure of the Arabic CUDQ was equivalent across sex, suggesting that the latent CUD construct has the same meaning in male and female adults. The highest CUDQ scores were reported by participants drinking 7 to 9 cups and 10 cups or more of coffee/per day relative to those consuming lower amounts of coffee. Finally, our findings revealed good concurrent validity based on positive correlations of CUDQ scores with nicotine dependence, depression and anxiety scores. Conclusion Overall, findings suggest that the CUDQ is appropriate and suitable for use to measure CUD among Arabic-speaking adults from the general population. Making the CUDQ available in the Arabic language can fill a gap in the assessment of problematic caffeine consumption in Arab contexts. Future studies are required to further confirm the psychometric soundness of the Arabic CUDQ in more representative samples, specific populations and other Arab countries.